Implementation of Generative Teaching Model to Improve Junior High School Studentsâ Mathematical Problem Solving Ability - Khasanah, Uswatun; Karso, Karso; Dahlan, Jarnawai Afgani (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The background of this study was the fact that studentsâ mathematical problem solving ability which was still low. The objectives of this study were: (1) determining whether the problem solving abilities of students under generative; teaching model were better than students under scientific teaching model or not; (2) determining quality of problem solving abilities of students under generative teaching model. A quasi-experimental with nonequivalent control group design was used as the research method. The participants of this study were 62 eighth graders of a junior high school in Bandung. The samples were two classes of students of the school; one class as the experimental group which was given generative teaching model, and the other as the control group which was given scientific teaching model. The data were obtained from mathematical problem solving test and observation. The results showed that: (1) the improvement of studentsâ mathematical problem solving under generative teaching model was better than students under scientific approach teaching.; (2) ) the quality of studentsâ problem solving abilities under generative teaching model and scientific teaching approach is middle.